An investigation on the mechanochemical behavior of the Ca–C–Cu2O–WO3 quaternary system to synthesize the Cu–WC nanocomposite powder. (January 2016) - Ebrahimi-Kahrizsangi, Reza; Mahabadi, Mohammadreza Kalani; Torabi, Omid
Abstract: Fundamental aspects of the reaction path in the Ca–C–Cu2 O–WO3 quaternary system to synthesize a copper matrix nanocomposite with reinforcement particles of tungsten carbide have been studied. The mechanism of reactions was specified through the analysis of the relevant sub-reactions. In the presence of carbon as a reducing agent (without Ca), the carbothermal reaction partially occurred even after 40 h of milling. On the other hand, calcium (without C) reduced both Cu2 O and WO3 after 15 min of milling in a self-sustaining mode. In the simultaneous presence of Ca and C, the products included Cu and W2 C as well as a significant amount of remaining unreacted W. The Cu–WC nanopowder, with no trace of W2 C, was synthesized by the addition of excess carbon to the initial mixture. SEM observations indicated that the composite powders were agglomerated and the range of the particle size was within 100 nm. Elemental mapping spectra showed a relatively uniform distribution of WC in the Cu matrix. Highlights: Cu–WC nanocomposite has been synthesized in Ca–C–Cu2 O–WO3 system. MSR mode reaction took place after 2 h milling time. The relevant sub-reactions were used to identify the reaction mechanism. The excess carbon content promotes the WC phase formation without W2 C. Nanoscale particles were obtained by mechanochemical technique.